PENINGKATAN KEMAMPUAN MENULIS TEKS BERITA MENGGUNAKAN MODEL STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) PADA SISWA KELAS VIII-C SMP SWASTA IMELDA MEDAN - Sanjuwita Sipayung; Dian Syahfitri (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Balikpapan, 2019)
This study aims to determine the improvement in learning outcomes of the ability to write news texts using the Student Teams Achievement Division (STAD) learning model in students of class VIII-C, Imelda Private Middle School, Medan Academic Year 2018/2019. The Student Teams Achievement Division (STAD) model is the development of the discussion learning model and is part of the cooperative learning model. In the context of learning the Student Teams Achievement Division (STAD) is applied by forming groups to begin the learning process. The reason for this research is that the lack of facilities and infrastructure has resulted in the ability to write news texts relatively low. This type of research used in research is descriptive qualitative research. The subject of the study was Indonesian Language teacher and students of class VIII-C, Imelda Medan Private Middle School. The results found were an increase in learning outcomes of the ability to write news texts using the Student Teams Achievement Division (STAD) model after going through two cycles with details of an increase from 65.94% complete to 83.27%.